2018
DOI: 10.19080/jojnhc.2018.08.555732
|View full text |Cite
|
Sign up to set email alerts
|

A Study of Population based Diabetes Registry in Developed Countries

Abstract: Background and Purpose: Diabetes mellitus is the most common metabolic dysfunction, which can cause serious complications when it is not well-controlled. Thus, the population-based diabetes registry results in controlling and preventing diabetes by providing continuous care of patients, establishing connection among care providers, and monitoring and maintaining the quality of care. Some developed countries such as the United States, England, Denmark, Sweden, Italy and Australia are considered as the pioneers … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

0
4
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 11 publications
0
4
0
Order By: Relevance
“…[26][27][28] The current study also showed a favorable effect of increased blood sugar monitoring on diabetic control. Finally it would be of immense importance to have a local and national registry and also to be part of international registries, this is not only deficient in Iraq but in the middle east in general, such registries can improve the understanding of diabetes and help benefit from experiences in the area and around the world, and give the opportunity for collaborative researches 29,30 of equal importance is having family targeted educational programs, which would have a positive effect on diabetic control. 31 We recommend performing a larger collaborative research on diabetic control including multiple centers in Iraq to have a more unified picture on the problems facing diabetic management in the country.…”
Section: Discussionmentioning
confidence: 99%
“…[26][27][28] The current study also showed a favorable effect of increased blood sugar monitoring on diabetic control. Finally it would be of immense importance to have a local and national registry and also to be part of international registries, this is not only deficient in Iraq but in the middle east in general, such registries can improve the understanding of diabetes and help benefit from experiences in the area and around the world, and give the opportunity for collaborative researches 29,30 of equal importance is having family targeted educational programs, which would have a positive effect on diabetic control. 31 We recommend performing a larger collaborative research on diabetic control including multiple centers in Iraq to have a more unified picture on the problems facing diabetic management in the country.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, establishing National Childhood Diabetes registries is pivotal to the Middle East Region, to advance research and ensure continued health care delivery to the highest standards. National Diabetes registries have been successfully implemented in developed countries such as the United States, Australia, and England (97). Interdisciplinary efforts by registries in these countries, where data is obtained from multiple sources such as physicians, regulatory bodies, national health centers, and other care providers have helped to control and manage the disease and reduce socioeconomic costs (98).…”
Section: Discussionmentioning
confidence: 99%
“…A disease registry is the continuous and systematic collection of information of all individuals in a specific population for whom a specific disease or health event has been diagnosed ( 12 ). Registries, as the main tool for managing disease data (including data collection, processing, and dissemination), use existing clinical guidelines and standards to reduce care delivery costs and help improve patient care delivery processes ( 10 , 11 , 13 , 14 ).…”
Section: Introductionmentioning
confidence: 99%
“…Hospital registry processes include case finding (identification and diagnosis of cases recorded and reported of disease in the registry), data collection and storage (collection and maintenance of patient information that may have been generated by physicians, and data recording and processing experts), abstracting (according to the scope of information recorded in this step, an abstracting about the disease, diagnosis, treatment and its consequences is recorded), patient follow-up (systematic process of monitoring and monitoring the health status of patients discharged from the hospital, reporting, (any type of reporting or analysis of data in the registry), and data quality control (a continuous process to monitor the quality of data entered in the registry to ensure data quality) ( 10 , 14 – 17 ).…”
Section: Introductionmentioning
confidence: 99%